Exploring the nuances of energy data in Python. (Manning Publications, 2021)
Energy companies forecast energy demand for their customers using time series and forecasting models to drive business decisions and insights. One of the keys to forecasting well is exploring your data. Here, Aric LaBarr explores some energy data to discover all the nuances we need for forecasting!.